2021
DOI: 10.4244/aij-d-21-00007
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aortic valve replacement for aortic regurgitation in Asians

Abstract: Aims: Although surgical aortic valve replacement (SAVR) is currently the recommended intervention for patients with native AR without aortic stenosis, a significant proportion of Asian patients undergo transcatheter aortic valve replacement (TAVR), which has not been studied fully for safety and outcomes. This systematic review aims to examine the characteristics and outcomes of Asian patients with pure native aortic regurgitation (AR) undergoing TAVR.Methods and results: PubMed, Embase, Scopus, Web of Science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…15 To address this problem, larger valves are usually selected, but oversized valves may increase the risk of valve rupture and atrioventricular block. 16 In fact, the prevalence of perivalvular leakage after TAVR in patients with severe AS has been reported, mild leakage predominating, but moderate or even severe leakage occurring in a significant number of patients. 17,18 This is because irregular calcification of the valve may cause the released prosthetic valve to not fit tightly to the original annulus structure, resulting in perivalvular leakage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 To address this problem, larger valves are usually selected, but oversized valves may increase the risk of valve rupture and atrioventricular block. 16 In fact, the prevalence of perivalvular leakage after TAVR in patients with severe AS has been reported, mild leakage predominating, but moderate or even severe leakage occurring in a significant number of patients. 17,18 This is because irregular calcification of the valve may cause the released prosthetic valve to not fit tightly to the original annulus structure, resulting in perivalvular leakage.…”
Section: Discussionmentioning
confidence: 99%
“…The main concern with using TAVR to treat AR patients is the difficulty in prosthetic valve anchoring due to insufficient calcification and/or annular enlargement 15 . To address this problem, larger valves are usually selected, but oversized valves may increase the risk of valve rupture and atrioventricular block 16 …”
Section: Discussionmentioning
confidence: 99%
“…Soong et al . 4 conducted a statistical study of TAVI for AR in Asians. The results indicated that TAVI has an acceptable safety and efficacy profile in native Asian patients with AR, with low mortality rates and generally good outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Transcatheter aortic valve implantation (TAVI) is established as an alternative to open surgery in patients with aortic stenosis (AS) and is gaining popularity for AR in high-risk AR patients who would not be good candidates for a surgical aortic valve replacement (SAVR). 4 Studies have been performed to compare in-hospital mortality between patients with SAVR versus TAVI, and no significant differences in outcomes were found. 5 Despite being a more challenging procedure, prior case reports have proven that TAVI for AR has been successfully performed on patients who have an LVAD.…”
Section: Introductionmentioning
confidence: 99%